Konsep Kurikulum Pendidikan islam Di pondok Pesantren Di Era Industri 4.0 - Bahiyah, Umamatul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
Educational institutions, both formal and non-formal, will need rules to regulate the educational process, in this case it can be referred to as the curriculum. Thus indirectly the curriculum is one of the instruments of educational institutions, including education in Islamic boarding schools or Islamic boarding schools, which are institutions that can be said to be a manifestation of the natural process of the development of the national education system. From a historical point of view, pesantren are not only synonymous with Islam, but also contain the meaning of Indonesian authenticity (indigenous). This is because an institution similar to a pesantren has actually existed since the Hindu-Buddhist era. So that Islam only has to continue and Islamize existing educational institutions. This type of research is a literature study. This literature study prioritizes and builds the Islamic Education Curriculum Concept at Islamic Boarding Schools in the Industrial Age 4.0. The concept of the idea of ​​Islamic Education Curriculum at Islamic Boarding Schools. The role of the Islamic education curriculum goes hand in hand with Islamic boarding schools as a place to gain Islamic knowledge. Pondok Pesantren is a place to provide space for self-actualization for someone who follows the instructions from the curriculum, both in terms of learning and enriching one's potential